Kidney, muscle and vascular structural and ultrastructural damages produced by toxic aggression of bee (Apis mellifera) venom - Rojas, Gladys; Rodríguez Acosta, Alexis; Finol, Héctor; Céspedes, Ghislaine; Hernández, Alipio (Revista Científica de la Facultad de Ciencias Veterinarias)
Bee (Apis mellifera) venom produces allergic local reaction and systemic reactions such as acute renal failure. The pathogenic mechanisms occurring in these accidents are still unclear. In this work the LD50 bee venom activity on kidney, skeletal muscle and renal vasculature of mice inoculated at 5, 10, 24 and 48 hours was studied. Necropsy specimens were obtained from kidney and sartorial muscles for light microscopy and electron microscopy studies. After 24 hours of exposure there was no evidence of structural changes on the kidney under light microscopy. Nevertheless, muscular tissue revealed lesions characterised by necrosis, phagocytosis and associated focal leukocyte inflammatory infiltration. In addition, mild regenerative activity and increase of the intermyofibrilar spaces in other muscular fibres were observed. From 5 to 48 hours there were ultrastructural changes on the kidney tissue. Showing early cellular swelling, non-uniform enlarging of the parietal or visceral glomerular membrane, tubular cell vacuolisation, capillary wall enlargment, haemoglobin presence in the lumen of the convoluted proximal tubules with later damage of sarcolemmal membrane. Changes in the muscular fibres were characterized by the presence of irregular and hyperchromatic nuclei and the sarcoplasma, augmented endothelial cytoplasm with prolongation toward the capillary lumen, muscular atrophy and partial loss of the sarcomeric striation. Besides to the increase of the intermyofibrillar spaces, prominent triads and pleomorphic mitochondria were evidenced. The subsarcolemmic nuclei were rounded and the nucleoli with diminished electronic density. The subsarcolemmic space was uncover, with abundant polysomes and mitochondria. An increase of the intermyofibrillar spaces, suggesting atrophy, was observed. The mitochondria were pleomorphic and electron dense. In some areas there was neither line M nor band H. Necrosis in muscle fibres was also observed, with the loss of the plasmatic membrane and cellular residues. The capillary endothelium of kidney vessels was altered with increment of the fenestrae. The capillary wall was augmented, with prolongation toward the lumen of the cytoplasm. These changes may be due to interactive effects of the multifactorial action of bee venom components (Phospholipase A2, mellitin, apamin and histamine).